A novel reactive-type joint torque sensor with high torsional stiffness for robot applications. (November 2019) - Min, Jae-Kyung; Ahn, Kuk-Hyun; Park, Hui-Chang; Song, Jae-Bok
Abstract: If a collaborative robot can measure contact force when in contact with the environment or humans, it can achieve better performance on collision detection, hand guiding, and force control. In order to achieve this, joint torque sensors are often mounted on each joint of a robot arm. However, a torque sensor mounted between the harmonic drive and the robot link suffers from crosstalk problems due to loads other than the torque of interest as well as the deformation of the harmonic drive during its power transmission. In addition, the torsional stiffness of a torque sensor itself tends to lower the overall stiffness of the arm, thereby affecting the accuracy of the robot. In this study, we propose a novel design of the strain gauge-based joint torque sensor that overcomes the shortcomings of conventional torque sensors. It is experimentally shown in various ways that the proposed joint torque sensor can properly deal with the crosstalk and thus accurately measure the torque of interest. Furthermore, it is found that the torsional stiffness of the sensor is large enough to minimize a reduction in overall arm stiffness, and its ring-type structure allows the sensor to be used without increasing the volume of the joint module.